Purtscher’s-like retinopathy as a rare complication of acute alcoholic pancreatitis - M. Wieczorek, Michalina; Caban, Miłosz; Fabisiak, Adam; Małecka-Panas, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Acute pancreatitis (AP) is one of the most frequent gastrointestinal causes of hospital admission [1, 2]. There are a lot of risk factors of AP, but 70–75% of all cases of AP result from alcohol abuse or cholelithiasis [3]. Severe abdominal pain, vomiting, and nausea are the main symptoms of AP [2, 4]. However, manifestation from other organs may occur in the course of this disease.